A comprehensive review of agrimoniin. Issue 1 (21st July 2017) - Grochowski, Daniel M.; Skalicka‐Woźniak, Krystyna; Orhan, Ilkay Erdogan; Xiao, Jianbo; Locatelli, Marcello; Piwowarski, Jakub P.; Granica, Sebastian; Tomczyk, Michał
Abstract: Plant tannins are a unique class of polyphenols with relatively high molecular weights. Within the ellagitannins group, agrimoniin––dimeric ellagitannin––is one of the most representative compounds found in many plant materials belonging to the Rosaceae family. Agrimoniin was first isolated in 1982 from roots of Agrimonia pilosa Ledeb. (Rosaceae), a plant traditionally used in Japan and China as an antidiarrheal, hemostatic, and antiparasitic agent. Agrimoniin is a constituent of medicinal plants, which are often applied orally in the form of infusions, decoctions, or tinctures. It is also present in commonly consumed food products, such as strawberries and raspberries. It is metabolized by human gut microbiota into a series of low‐molecular‐weight urolithins with proven anti‐inflammatory and anticancer in vivo and in vitro bioactivities. The compound has received widespread interest owing to some interesting biological effects and therapeutic activities, which we elaborate in the present review. Additionally, we present an overview of the techniques used for the analysis, isolation, and separation of agrimoniin from the practical perspective.